Risk factors of hypoglycaemia in type 1 diabetes individuals during intensive sport exercise—Data from the SPORTGIVECHANCE event. Issue 11 (4th September 2019) - Hohendorff, Jerzy; Ucieklak, Damian; Skupien, Jan; Matejko, Bartlomiej; Di Giacomo, Angelica; Malecki, Maciej T.; Klupa, Tomasz
Abstract: Aims: Fear of hypoglycaemia seems to be one of the strongest barrier to physical activity for individuals with type 1 diabetes mellitus (T1DM).The aim of the study was to describe clinical characteristics of participants with T1DM in the intense sporting event of runs and bike rides"SPORTGIVECHANCE—Diabetic runners and cyclists for more sport for all in Europe", and investigate factors associated with self‐reported hypoglycaemia episodes during the competition, in particular the use of continuous and flash glucose monitoring systems (CGM/FGM). Methods: The sporting event took place in Spoleto, Italy from 30 August 2018 to 2 September 2018. An online survey was distributed among 150 participants with diabetes. Only T1DM patients were invited to complete the survey that included questions on baseline clinical characteristics as well as glucose control and meal related issues during the competition. Logistic regression was used to determine factors associated with reported hypoglycaemia. Results: There were 35 T1DM individuals who completed the questionnaire: eight subjects were continuous glucose monitoring system (CGM) users, 10 used flash glucose monitoring systems (FGM), while the others performed self‐measured blood glucose measurements (SMBG) on glucose meters. Mild hypoglycaemia episodes during the competition were reported by four CGM/FGM users and six non‐users (OR: 0.73, CI: 0.34‐1.53). No severe hypoglycaemic episode was reported. Body mass index (BMI) (OR: 1.47, CI: 1.01‐2.13) and subjectively very hard or maximal intensity of the competition (OR: 4.90, CI: 1.51‐15.89) were associated with a higher risk of hypoglycaemia. Conclusions: Data obtained from the self‐selected sample of T1DM patients suggests that T1DM individuals can participate in intense sport competitions with moderate risk of mild hypoglycaemia regardless of CGM/FGM or SMBG use.